Biochemical differences based on sex and clusters of biomarkers in patients with COVID-19: analysis from the CARDIO COVID 19–20 registry - Frank Cañón-Estrada; Juan Andrés Muñoz-Ordoñez; Manuela Escalante-Forero; Yorlany Rodas; Andrea Alejandra Arteaga-Tobar; Valeria Azcarate-Rodriguez; Eduardo Perna; Iván Mendoza; Fernando Wyss; José Luis Barisani; Mario Speranza; Walter Alarco; et al. (BMC Cardiovascular Disorders, 2025)
Abstract Background The inflammatory response associated with COVID-19 varies with sex, potentially affecting disease outcomes. Males have a higher risk of complications compared to females, requiring an evaluation of differences in inflammatory response severity based on sex. Objective To compare clinical data, biochemical biomarkers, and outcomes among hospitalized COVID-19 patients in Latin America and the Caribbean (LA&C) based on sex and to perform a cluster analysis of biomarker profiles for both sexes. Methods This prospective, multicenter observational registry made by the Inter-American Council of Heart Failure and Pulmonary Hypertension of the Inter-American Society of Cardiology included hospitalized COVID-19 patients from 44 hospitals in 14 countries in LA&C between May 1, 2020, and June 30, 2021. Results Of 3,260 patients (1,201 females and 2,059 males), males had higher C-reactive protein and ferritin levels, while females had higher natriuretic peptides and d-dimer levels. Males had more cardiovascular complications (acute coronary syndrome [3.3% vs. 2.2%], decompensated heart failure [8.9% vs. 7.8%], pulmonary embolism [4.4% vs. 2.9%]), intensive care unit (ICU) admissions (56.9% vs. 47.7%), and overall mortality (27.5% vs. 22.1%). Cluster analysis identified three groups: one with normal-range biomarkers but elevated ferritin, one with coagulation abnormalities, and one with an inflammatory profile linked to renal injury and increased non-cardiovascular mortality. Conclusions In the LA&C population hospitalized with COVID-19, males had higher inflammatory biomarker levels, correlating with increased cardiovascular complications and mortality. The cluster with an inflammatory profile showed higher non-cardiovascular mortality, while clusters with elevated ferritin levels were associated with increased ICU admissions.